Digitalization on Studies by Millenials Researcher - Afifah, Lilis (KnE Social Sciences, 2020)
Echo boomers or generation ME, better known as ‘Millennials’, are people whose daily activities are inseparable from the involvement of technological and information developments. The dependence of echo boomers on modern technology in every line of life is not necessarily parallel to their interest in conducting research on this subject. Therefore, it is necessary to conduct a study that examines the involvement of digitalization in the research of millennial generations. The data sources used in this study were German Department students consisting of students of German study programs and Chinese study programs as well as thesis works produced by students from both study programs between 2015 and 2019. The research data was obtained through interviews and documentation, and the findings data analyzed qualitatively. The results showed that there were not many studies by students involving information technology. The role of digitalization is mostly found in research on the development of learning media, a small portion of which occurs in the application of teaching materials and learning media. Keywords: digitalization, research, millenial generation